Reorienting Educational Management Information Systems for Resilient Digital Learning Ecosystems in Industry 5.0 - Indah Naela Zulfa; Indi Mazaya; Inda Millata Afna; Tsania Karima Khusna; Norma Kartika Putri; Raya Ajeng Pertiwi; Mutiah Puspita Andiny; Muhammad Ikmal Irsyadul Fairus; Rani Suci Rahmadani; Diva Agi Septiana; Mansur Chadi Mursid (Universitas Negeri Yogyakarta, 2026)
The transition toward Industry 5.0 has encouraged educational institutions to reconsider the role of Management Information Systems (MIS) beyond administrative efficiency and technological automation. This study investigates how MIS can be reoriented to support human-centered values and organizational resilience within increasingly complex digital learning environments. A Systematic Literature Review (SLR) was conducted following the PRISMA framework, complemented by bibliometric mapping using VOSviewer. Relevant publications published between 2021 and 2025 were collected from reputable national and international databases and analyzed to identify major research trends, conceptual relationships, and emerging gaps. The findings reveal that existing studies predominantly emphasize technological innovation, while the dimensions of human-centricity and resilience remain insufficiently integrated into educational MIS research. The literature also highlights the growing need for information systems capable of maintaining institutional adaptability, learning continuity, and stakeholder well-being amid rapid technological and social change. In response to these challenges, this study develops the SIM 5.0 conceptual framework, which combines three interrelated dimensions: technological capability, human-centered design, and system resilience. The framework suggests that the effectiveness of educational MIS depends not only on technological advancement but also on its capacity to support educators, students, and administrative personnel while responding flexibly to evolving educational demands. These findings provide practical guidance for developing sustainable, adaptive, and learner-oriented digital management systems in educational institutions.